Child Development Levels of Stunting Children Under Five Years: A Case Study in Indonesia - Utami, Wiwik; Rashid, Norhashima Abd; Afandi, Agus Ari; Patonah, Siti; Mulyani, Sri (International Journal of Nursing Information, 2024)
Children under five years of age who experience stunting are at risk of experiencing physical, mental, social, and language development barriers. Non-pharmacological approaches to stunting are essential because stunting refers to a lack of growth in children. Therefore, a developmental examination, namely a pre-developmental screening questionnaire, must be conducted to identify non-pharmacological needs. The research aims to identify the development of stunted children. Descriptive research design, the population of all children experiencing stunting in the working area of the Mejuwet Health Center, Bojonegoro Regency, in 2023. The sample was 29 respondents, with purposive sampling. Data were collected using questionnaire sheets, and then editing, coding, scoring, and tabulating were carried out, followed by analysis. The results of the study showed that 31% of respondents with stunted children under the age of five experienced deviant development, 55.2% had questionable development, and only 18.3% had development that was appropriate for their age. Appropriate stimulation for the growth and development of children aged 48-59 months consists of several important activities, namely stimulation of gross motor skills, fine motor skills, speech and language, socialization, and independence. By involving children in these activities, we can help stimulate their development holistically. Monitor the child's growth and development regularly by having regular check-ups with health workers. The contribution of this research is recommended that the child's mother utilizes a non-pharmacological approach by providing support by inviting the stunted child to play puzzles, draw, color, and write to increase creativity, support speech, and increase socialization with peers.